Chamilo LMS for web-based e-learning development in a vocational high school - Faiza Rini; Ang Ling Weay; Rini Novita; Ridho Illahi (Researcher and Lecturer Society, 2024)
The development of a web-based e-learning at SMK Negeri 4 Padang was initiated by the absence of a structured e-learning system at the school. This study aims to design and implement e-learning using the Chamilo Learning Management System (LMS) platform, ensuring its validity and practicality. The study employs Research and Development (R&D), adapting 3 stages of the ADDIE model, including analyzing, designing, and developing. The results of the validity test, assessed by three lecturers as media validators, show a score of 91.84%, categorized as very valid. The practicality test results show that 92.31% of teachers and 82.34% of students rated the system on the very practical category. Based on this data, the developed e-learning system at SMK Negeri 4 Padang is considered valid and practical. However, this study has not been through the broader implementation and evaluation. Therefore, it is suggested for further researchers conducting the similar studies to get it come to the whole stages of ADDIE model, confirming its effectiveness.